Securing Medication Use in Pediatric Oncology Units in French-Speaking Africa: MAEva Pilot Program Results in Ivory Coast - Line Couitchere; Innocent Krasse; Léa Zaho; Marina Yao; Guy Yao; Carole Coze; Nadine Robert; Olga Molly; Max N'Doumy; Charles Akoun; Bertrand Pourroy (JCO Global Oncology)
PURPOSEMedication use is a significant global risk for patients, particularly in African hospitals. The aim of this study was to adapt and implement a proactive risk assessment tool for medication use in pediatric oncology units in French-speaking Africa to reduce medication errors and enhance patient safety.METHODSThe médiEval French tool was adapted into the MAEva tool for the African context through a three-stage process: content review by a multidisciplinary group, content formatting, and item modification/validation. Three Excel-based grids (prescription, administration, and dispensing) were used, each audited by external experts to ensure validity and functionality. Initial audits using the MAEva tool were conducted in June 2022. The auditor assessed two pediatric oncologists, a pharmacist, and two nurses. Postaudit results were immediately shared to highlight weaknesses and strengths and to build an action plan. This plan was monitored through regular meetings, and a second audit occurred in September 2023 after implementation.RESULTSThe MAEva grids retained the médiEval tool's structure but adapted 16 of 174 items for the African context. Initial risk levels were high: 29%-34% for prescription, 33% for dispensing, and 44%-45% for administration. A 14-item action plan was created on the basis of audit results, focusing on practical measures without significant financial investment. By September 2023, 54% of the action plan was completed, leading to significant risk reductions: 18 points in prescription, 10 in dispensing, and 26 in administration.CONCLUSIONThe adaptation and implementation of the MAEva tool significantly reduced overall risk levels across all processes, demonstrating the effectiveness of the action plan and the tool's applicability in an African context. MAEva's proactive risk assessment approach proved effective and feasible without substantial financial investment.